2023
DOI: 10.3390/life13041066
|View full text |Cite
|
Sign up to set email alerts
|

Afamelanotide Is Associated with Dose-Dependent Protective Effect from Liver Damage Related to Erythropoietic Protoporphyria

Abstract: In animal models, melanocyte-stimulating hormones (MSHs) protect the liver from various injuries. Erythropoietic protoporphyria (EPP), a metabolic disorder, leads to the accumulation of protoporphyrin (PPIX). In addition to the most prominent symptom of incapacitating phototoxic skin reactions, 20% of EPP patients exhibit disturbed liver functioning and 4% experience terminal liver failure caused by the hepatobiliary elimination of excess PPIX. Skin symptoms are mitigated through the application of the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…In the present study, we did not detect any decreases in protoporphyrin levels or reductions in liver biochemistry values during treatment with afamelanotide, in contrast to one European cohort, although our study population was smaller and included fewer longitudinal values [13]. In fact, we found that metal-free erythrocyte protoporphyrin levels rose slightly during treatment compared with baseline levels, which we suspect to be related to natural variation and not a medication effect.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we did not detect any decreases in protoporphyrin levels or reductions in liver biochemistry values during treatment with afamelanotide, in contrast to one European cohort, although our study population was smaller and included fewer longitudinal values [13]. In fact, we found that metal-free erythrocyte protoporphyrin levels rose slightly during treatment compared with baseline levels, which we suspect to be related to natural variation and not a medication effect.…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, we only present data on AST, ALT, and total bilirubin, and these liver biochemistries may be within the normal range even in patients with protoporphyria-related liver disease [ 14 ]. We collected these labs for clinical reasons at least once yearly, but not with each afamelanotide dose, as performed in another study [ 13 ]. Moreover, metal-free protoporphyrin levels vary by as much as 25% within the same patient over time, which could influence the variability in these results, especially as our data are presented in aggregate [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has higher potency and stability than the natural MSH peptide. A recent observational animal study from Switzerland suggests the occurrence of a dose-dependent protective effect from liver damage related to EPP [ 32 ]. Afamelanotide is administered as a subcutaneous implant, which is injected every two months and gradually releases the active peptide.…”
Section: Previous Therapiesmentioning
confidence: 99%